A hydrophilic coating, preparation method and device
By using silicone monomers on the surface of the substrate for chemical vapor deposition of hot wires, a coating with excellent hydrophilicity and hydrophilic retention in high humidity environments is formed, which solves the problem that the existing coating loses superhydrophilic properties in high humidity environments, improves the wear resistance and water immersion resistance of the coating, and enhances its application performance.
Patent Information
- Application Number
- CN202211657189.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-12-22
AI Technical Summary
The existing hydrophilic coatings lose their superhydrophilic properties in high humidity environments, and have poor wear resistance and water immersion resistance, which limits their application in the fields of anti-fog and self-cleaning.
By performing chemical vapor deposition of hot wires under an oxygen atmosphere using silicone monomer on the surface of the substrate, a coating with excellent hydrophilicity and hydrophilic retention in a high humidity environment is formed.
The hydrophilic retention of the coating in a high humidity environment is achieved, and the water contact angle is maintained below 10°, which enhances the wear resistance and water immersion resistance of the coating, thereby improving its application performance in the fields of anti-fog and self-cleaning.
Smart Images

Figure CN118239694B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of hot wire chemical vapor deposition, and in particular to a hot wire chemical vapor deposition hydrophilic coating, a preparation method and a device. Background Art
[0002] Preparing a hydrophilic polymer coating on the surface of a substrate is one of the most widely used methods for preparing a hydrophilic coating. The surface of such a hydrophilic polymer coating usually contains a large number of hydrophilic groups (atomic groups or ionic groups such as -OH, -COOH and -NH2 that can form hydrogen bonds), which makes the coating hydrophilic and water-absorbing.
[0003] For example, it is reported in the literature that a uniform mixture of hydroxyethyl methacrylate, methacrylic acid, benzoyl peroxide and ethylene glycol monoethyl ether is reacted at 65°C for 6 to 8 hours under nitrogen protection, and then the mixture is diluted to 10% concentration, a small amount of ethylene glycol dimethacrylate and benzoyl peroxide are added, and the mixture is sprayed on the surface of the substrate and dried at room temperature for 1-2 hours, and finally dried at 120°C for 1 to 2 hours, and cooled to room temperature to obtain a super hydrophilic surface. However, the surface of the super hydrophilic coating prepared by this type of polymer material with hydrophilic groups has poor wear resistance and is extremely intolerant to water immersion. In a high humidity environment, the surface of the coating is saturated with water, and the water contact angle is easily increased, causing the coating to lose its super hydrophilic properties. The water resistance and moisture resistance of the super hydrophilic property greatly reduce the application of super hydrophilic coatings in the fields of anti-fog and self-cleaning. Summary of the invention
[0004] The specific embodiment of the present invention provides a hydrophilic coating, preparation method and device having excellent hydrophilicity and excellent hydrophilicity retention in a high humidity environment. The specific scheme is as follows:
[0005] A hydrophilic coating has a water contact angle of less than 10° and is formed by depositing an organic silicon monomer on a substrate surface through hot wire chemical vapor deposition in an oxygen atmosphere.
[0006] Optionally, the water contact angle of the hydrophilic coating is below 5°.
[0007] Optionally, the water contact angle of the hydrophilic coating after being immersed in water at room temperature for 120 minutes is below 10°.
[0008] Optionally, the organosilicon monomer is selected from at least one of the structures in the following formulas (1) to (3):
[0009]
[0010] In the above formulae (1) to (3), R1, R5 and R9 are independently selected from C1-C 10 Alkyl or C1-C10 Alkoxy, R2, R3, R4, R6 and R 10 are independently selected from hydrogen atoms, C1-C 10 Alkyl or C1-C 10 Alkoxy, R7 is a hydrogen atom, a hydroxyl group, a C1-C 10 Alkyl or C1-C 10 Alkoxy, R8 is a hydrogen atom or a C1-C 10 wherein n is an integer from 1 to 10, and m is an integer from 1 to 10.
[0011] Optionally, the organosilicon monomer has a structure as shown in formula (1), and R1, R2, R3 and R4 are independently selected from C1-C4 alkoxy groups.
[0012] Optionally, the organic silicon monomer is ethyl orthosilicate, tetramethoxysilane, propyl orthosilicate or butyl orthosilicate.
[0013] Optionally, the boiling point of the organosilicon monomer is below 200°C.
[0014] Optionally, the hydrophilic coating has a thickness of 5 to 3000 nm.
[0015] A method for preparing the hydrophilic coating as described above comprises the following steps:
[0016] placing the substrate on a sample stage with a cooling device in a vacuum deposition chamber;
[0017] The vacuum deposition chamber is evacuated, oxygen, inert gas and organosilicon monomer gas are introduced, and the heating wire heating and the cooling device are turned on to carry out the hot wire chemical vapor deposition.
[0018] Optionally, the heating wire is a metal wire containing at least one of nickel, chromium or tungsten.
[0019] Optionally, the temperature of the sample stage is controlled below 100°C, and the temperature of the heating wire is 200-900°C.
[0020] Optionally, the method further includes the following steps: before the hot wire chemical vapor deposition, performing plasma pre-treatment on the surface of the substrate.
[0021] Optionally, the method further includes the following steps: after the hot wire chemical vapor deposition, performing plasma post-treatment on the surface of the coating deposited by the hot wire chemical vapor deposition in an oxygen atmosphere.
[0022] Optionally, the plasma is a dual-electrode pulsed plasma.
[0023] A device, at least part of the surface of which has the hydrophilic coating as described above.
[0024] The hydrophilic coating of a specific embodiment of the present invention is formed by hot wire chemical vapor deposition of silicone monomers on the surface of a substrate under an atmosphere containing oxygen. The hydrophilic coating has excellent hydrophilic properties, a water contact angle of less than 10°, and excellent hydrophilic retention in a high humidity environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the anti-fog test result diagram of Example 1;
[0026] Figure 2 This is the anti-fog test result diagram of Example 2;
[0027] Figure 3 This is the anti-fog test result diagram of Example 3. DETAILED DESCRIPTION
[0028] A specific embodiment of the present invention provides a hydrophilic coating, wherein the water contact angle of the hydrophilic coating is below 10°, and the hydrophilic coating is formed by hot wire chemical vapor deposition of organic silicon monomers on the surface of a substrate in an atmosphere containing oxygen.
[0029] The hydrophilic coating of the specific embodiment of the present invention is deposited by hot wire chemical vapor deposition. The silicone monomer can form an excellent hydrophilic coating on the surface of the substrate under the catalytic reaction of the heated metal hot wire under oxygen atmosphere conditions, and the hydrophilic coating has excellent hydrophilic retention in a high humidity environment.
[0030] The water contact angle of the hydrophilic coating in a specific embodiment of the present invention is obtained by testing according to the GB / T30447-2013 standard. In some specific embodiments, the water contact angle of the hydrophilic coating is below 5°.
[0031] The hydrophilic coating of a specific embodiment of the present invention has excellent hydrophilic retention in a high humidity environment. In some specific embodiments, the water contact angle of the hydrophilic coating after being immersed in water at room temperature for 120 minutes is below 10°. In some specific embodiments, the water contact angle of the hydrophilic coating after being immersed in water at room temperature for 120 minutes is below 5°.
[0032] The hydrophilic coating of a specific embodiment of the present invention has excellent hydrophilic retention in a high humidity environment. In some specific embodiments, the water contact angle change rate of the hydrophilic coating after immersion in water at room temperature for 10 minutes is no more than 30%. In some specific embodiments, the water contact angle change rate of the hydrophilic coating after immersion in water at room temperature for 10 minutes is no more than 20%. In some specific embodiments, the water contact angle change rate of the hydrophilic coating after immersion in water at room temperature for 10 minutes is no more than 10%. In some specific embodiments, the water contact angle change rate of the hydrophilic coating after immersion in water at room temperature for 10 minutes is no more than 5%.
[0033] In some embodiments of the hydrophilic coating of the present invention, the organosilicon monomer has a structure shown in the following formula (1):
[0034]
[0035] In formula (1), R1 is selected from C1-C 10 Alkyl or C1-C 10 R2, R3 and R4 are independently selected from hydrogen atoms, C1-C 10 Alkyl or C1-C 10 In some embodiments, R1 is selected from C1-C4 alkyl or C1-C4 alkoxy, R2, R3 and R4 are independently selected from hydrogen atom, C1-C4 alkyl or C1-C4 alkoxy, the C1-C4 alkyl is specifically methyl, ethyl, propyl, butyl or isobutyl, or C1-C4 alkoxy, the C1-C4 alkoxy is specifically methoxy, ethoxy, propoxy, butoxy or isobutyl. In some embodiments, R1, R2, R3 and R4 are independently selected from C1-C4 alkoxy, in some embodiments, the organosilicon monomer is ethyl orthosilicate, tetramethoxysilane, propyl orthosilicate or butyl orthosilicate.
[0036] In some embodiments of the hydrophilic coating of the present invention, the organosilicon monomer has a structure shown in the following formula (2):
[0037]
[0038] In formula (2), R5 is selected from C1-C 10 Alkyl or C1-C 10 Alkoxy, R6 is selected from hydrogen atom, C1-C 10 Alkyl or C1-C 10 Alkoxy, R7 is a hydrogen atom, a hydroxyl group, a C1-C 10 Alkyl or C1-C10 Alkoxy, R8 is a hydrogen atom or a C1-C 10 alkyl, n is an integer from 1 to 10, specifically 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10. In some specific embodiments, the R5 is selected from C1-C4 alkyl or C1-C4 alkoxy, R6 is selected from hydrogen atom, C1-C4 alkyl or C1-C4 alkoxy, R7 is hydrogen atom, hydroxyl, C1-C4 alkyl or C1-C4 alkoxy, R8 is hydrogen atom or C1-C4 alkyl, the C1-C4 alkyl is specifically methyl, ethyl, propyl, butyl or isobutyl, or C1-C4 alkoxy, the C1-C4 alkoxy is specifically methoxy, ethoxy, propoxy, butoxy or isobutoxy.
[0039] In some embodiments of the hydrophilic coating of the present invention, the organosilicon monomer has a structure shown in the following formula (3):
[0040]
[0041] In formula (3), R9 is selected from C1-C 10 Alkyl or C1-C 10 The alkoxy group, R 10 Selected from hydrogen atoms, C1-C 10 Alkyl or C1-C 10 alkoxy, m is an integer from 1 to 10, specifically 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10. In some specific embodiments, R9 is selected from C1-C4 alkyl or C1-C4 alkoxy, R 10 It is selected from a hydrogen atom, a C1-C4 alkyl group or a C1-C4 alkoxy group, wherein the C1-C4 alkyl group is specifically exemplified by a methyl group, an ethyl group, a propyl group, a butyl group or an isobutyl group, or a C1-C4 alkoxy group, wherein the C1-C4 alkoxy group is specifically exemplified by a methoxy group, an ethoxy group, a propoxy group, a butoxy group or an isobutoxy group.
[0042] In the hydrophilic coating of the specific embodiment of the present invention, in order to facilitate the evaporation and gasification of the organosilicon monomer, in some specific embodiments, the boiling point of the organosilicon monomer is below 200°C.
[0043] The hydrophilic coating of the specific embodiment of the present invention has a thickness of nanometer level. In some specific embodiments, the thickness of the coating is 1 to 3000 nm. In some specific embodiments, the thickness of the coating is 5 to 500 nm. In some specific embodiments, the thickness of the coating is 5 to 150 nm.
[0044] In some embodiments of the hydrophilic coating of the specific embodiment of the present invention, the substrate is metal, ceramic, plastic, glass, electronic equipment or optical instrument, etc. In some embodiments, the substrate is a transparent material, for example, it can be a lens of glasses, goggles, laser protective glasses, telescopes and lenses of various camera equipment, observation windows of various machines, sports diving goggles, bathroom glass, chemical or biological protective masks, vehicle windshields and rearview mirrors, explosive disposal protection equipment, helmets, solar panels, observation windows of measuring instruments, glass covers, glass walls of greenhouses, etc.
[0045] A specific embodiment of the present invention also provides a method for preparing the hydrophilic coating as described above, comprising the following steps:
[0046] placing the substrate on a sample stage with a cooling device in a vacuum deposition chamber;
[0047] The vacuum deposition chamber is evacuated, oxygen, inert gas and organosilicon monomer gas are introduced, and the heating wire heating and the cooling device are turned on to carry out the hot wire chemical vapor deposition.
[0048] In the method for preparing a hydrophilic coating according to a specific embodiment of the present invention, in some specific embodiments, the heating wire is a metal wire containing at least one of nickel, chromium or tungsten, for example, it can be nickel wire, chromium wire, tungsten wire, nickel-chromium wire or nickel-tungsten wire, etc.
[0049] In the method for preparing a hydrophilic coating according to a specific embodiment of the present invention, in some specific embodiments, the temperature of the sample stage is controlled below 100°C, in some specific embodiments, the temperature of the sample stage is controlled at 20-50°C, for example, it can be 20°C, 30°C, 40°C or 50°C, etc. In some specific embodiments, the cooling device of the sample stage adopts a water cooling device.
[0050] In the method for preparing a hydrophilic coating according to a specific embodiment of the present invention, in some specific embodiments, the temperature of the heating wire is 200°C to 900°C, for example, it can be 200°C, 250°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C or 900°C, etc.
[0051] In the method for preparing a hydrophilic coating of a specific embodiment of the present invention, the vacuum degree of the vacuum deposition chamber can be set according to actual conditions. In some specific embodiments, the vacuum degree is 0.1 to 1000 mTorr, in some specific embodiments, the vacuum degree is 1 to 100 mTorr, and in some specific embodiments, the vacuum degree is 5 to 50 mTorr.
[0052] In the method for preparing a hydrophilic coating of a specific embodiment of the present invention, the inert gas includes nitrogen, helium, neon or argon, etc. In some specific embodiments, the flow rate of the inert gas is 0 to 1000 sccm, in some specific embodiments, the flow rate of the inert gas is 5 to 500 sccm, and in some specific embodiments, the flow rate of the inert gas is 50 to 200 sccm.
[0053] In the method for preparing a hydrophilic coating according to a specific embodiment of the present invention, in some specific embodiments, the flow rate of the inert gas is 1 to 1000 sccm, in some specific embodiments, the flow rate of the inert gas is 5 to 500 sccm, and in some specific embodiments, the flow rate of the inert gas is 50 to 200 sccm.
[0054] The preparation method of the hydrophilic coating of the specific embodiment of the present invention, in some specific embodiments, the preparation method of the hydrophilic coating also includes the following steps: before the hot wire chemical vapor deposition, the surface of the substrate is subjected to plasma pretreatment. In some specific embodiments, the plasma is a dual-electrode pulsed plasma. Through the plasma pretreatment, the hydrophilicity of the hydrophilic coating and the hydrophilic retention in a high humidity environment can be further effectively improved. In some specific embodiments, the discharge power of the pulsed plasma is 10 to 1000 W, the discharge time is 10 to 1000 s, the pulse frequency is 1 to 1000 Hz, and the pulse duty cycle is 1:1 to 1:500. In some specific embodiments, the discharge power of the pulsed plasma is 100 to 500 W, the discharge time is 100 to 500 s, the pulse frequency is 10 to 500 Hz, and the pulse duty cycle is 1:10 to 1:100.
[0055] The method for preparing a hydrophilic coating according to a specific embodiment of the present invention, in some specific embodiments, the plasma pretreatment is carried out in an atmosphere having oxygen, in some specific embodiments, the plasma pretreatment is carried out in an atmosphere having an inert gas, and in some specific embodiments, the plasma pretreatment is carried out in an atmosphere having oxygen and an inert gas.
[0056] The preparation method of the hydrophilic coating of the specific embodiment of the present invention, in some specific embodiments, the preparation method of the hydrophilic coating also includes the following steps: after the hot wire chemical vapor deposition, in an oxygen atmosphere, the surface of the coating deposited by the hot wire chemical vapor deposition is subjected to plasma post-treatment. In some specific embodiments, the plasma is a dual-electrode pulsed plasma. Through the plasma post-treatment, the hydrophilicity of the hydrophilic coating and the hydrophilic retention in a high humidity environment can be further effectively improved. In some specific embodiments, the discharge power of the pulsed plasma is 10 to 1000 W, the discharge time is 1 to 1000 s, the pulse frequency is 1 to 1000 Hz, and the pulse duty cycle is 1:1 to 1:500. In some specific embodiments, the discharge power of the pulsed plasma is 100 to 500 W, the discharge time is 10 to 500 s, the pulse frequency is 10 to 500 Hz, and the pulse duty cycle is 1:10 to 1:100.
[0057] In the method for preparing a hydrophilic coating according to a specific embodiment of the present invention, in some specific embodiments, a pair or more copper electrodes are provided in the vacuum deposition chamber, and before and after the hot wire chemical vapor deposition, the copper electrodes are turned on, and the plasma pre-treatment and plasma post-treatment processes are directly carried out in the vacuum deposition chamber.
[0058] The method for preparing a hydrophilic coating according to a specific embodiment of the present invention, in some specific embodiments, the organosilicon monomer enters the vaporization chamber for vaporization and is then introduced into the vacuum deposition chamber, in some specific embodiments, the organosilicon monomer enters the vaporization chamber at a certain flow rate, in some specific embodiments, the organosilicon monomer enters the vaporization chamber in multiple batches, in some specific embodiments, the flow rate of the organosilicon monomer entering the vaporization chamber is 10-2400 μL / min, and in some specific embodiments, the flow rate of the organosilicon monomer entering the vaporization chamber is 100-500 μL / min.
[0059] The method for preparing the hydrophilic coating according to the specific embodiment of the present invention, the hydrophilic coating, the organosilicon monomer and the substrate are described as above.
[0060] A specific embodiment of the present invention further provides a device, wherein at least a portion of the surface of the device has the above-mentioned hydrophilic coating. In some specific embodiments, the above-mentioned hydrophilic coating is deposited on a portion of the surface or the entire surface of the device.
[0061] The present disclosure is further described below through specific embodiments.
[0062] Example
[0063] Test Method Description
[0064] Coating thickness test: Use the American Filmetrics F20-UV-film thickness measuring instrument for testing.
[0065] Water contact angle test: Tested according to GB / T 30447-2013 standard.
[0066] Anti-fog test: Place the glass plate sample on a 95℃ constant temperature water bath with the coating surface facing the water vapor. The distance between the water surface and the coating surface is 5cm. Observe whether fogging occurs after 10 minutes.
[0067] Example 1
[0068] A transparent glass plate (length: 13 cm, width: 6.5 cm, thickness: 1 mm) and a silicon wafer were placed on a sample stage of a vacuum deposition chamber equipped with a pair of copper rod electrodes. The vacuum deposition chamber was evacuated to a vacuum degree of 8 mTorr, and the temperature of the sample stage was controlled to about 30°C by water cooling. At the same time, helium and oxygen were introduced at a flow rate of 90 sccm each, and the chamber pressure was 100 mTorr.
[0069] The copper rod electrode pulse plasma discharge was turned on to pretreat the surface of the transparent glass plate. The discharge time was 240s and the discharge power was 400W.
[0070] Turn off the copper rod electrode plasma discharge, turn on the nickel-chromium hot wire power supply, and control the hot wire temperature to 300°C; after tetraethyl orthosilicate (TEOS) is vaporized at a temperature of 110°C, it is introduced into the vacuum deposition chamber at a flow rate of 300μl / min; at the same time, keep the water-cooled sample stage temperature, cavity pressure, and helium and oxygen flow rates unchanged.
[0071] After the coating was completed, the temperature and vacuum were maintained unchanged. After 30 minutes, the vacuum was broken and the silicon wafer and glass plate samples were taken out. The coating thickness of the silicon wafer was tested. The water contact angle test results of the coating on the glass plate samples are listed in Table 1 below. At room temperature, the glass plate samples were immersed in water for different time periods and then naturally dried. The water contact angle test results are listed in Table 2 below. The anti-fog test results of the coated (coated) glass plate samples and the uncoated blank glass plate samples are shown in Table 2 below. Figure 1 shown.
[0072] Example 2
[0073] A transparent glass plate (length: 13 cm, width: 6.5 cm, thickness: 1 mm) and a silicon wafer were placed on a sample stage of a vacuum deposition chamber equipped with a pair of copper rod electrodes. The vacuum deposition chamber was evacuated to a vacuum degree of 8 mTorr, and the temperature of the sample stage was controlled to about 30°C by water cooling. At the same time, helium and oxygen were introduced at a flow rate of 90 sccm each, and the chamber pressure was 100 mTorr.
[0074] The nickel-chromium hot wire power supply was turned on and the hot wire temperature was controlled to be 300°C; tetraethyl orthosilicate (TEOS) was vaporized at a temperature of 110°C and introduced into the vacuum deposition chamber at a flow rate of 300 μl / min; at the same time, the temperature of the water-cooled sample stage, the chamber pressure, and the flow rates of helium and oxygen were kept unchanged;
[0075] After the coating was completed, the temperature and vacuum were maintained unchanged. After 30 minutes, the vacuum was broken and the silicon wafer and glass plate samples were taken out. The coating thickness of the silicon wafer was tested. The water contact angle test results of the coating on the glass plate samples are listed in Table 1 below. At room temperature, the glass plate samples were immersed in water for different time periods and then naturally dried. The water contact angle test results are listed in Table 2 below. The anti-fog test results of the coated (coated) glass plate samples and the uncoated blank glass plate samples are shown in Table 2 below. Figure 2 shown.
[0076] Example 3
[0077] A transparent glass plate (length: 13 cm, width: 6.5 cm, thickness: 1 mm) and a silicon wafer were placed on a sample stage of a vacuum deposition chamber equipped with a pair of copper rod electrodes. The vacuum deposition chamber was evacuated to a vacuum degree of 8 mTorr, and the temperature of the sample stage was controlled to about 30°C by water cooling. At the same time, helium and oxygen were introduced at a flow rate of 90 sccm each, and the chamber pressure was 100 mTorr.
[0078] The copper rod electrode pulse plasma discharge was turned on to pretreat the surface of the transparent glass plate. The discharge time was 240s and the discharge power was 400W.
[0079] The copper rod electrode plasma discharge was turned off, and the nickel-chromium hot wire power supply was turned on, and the hot wire temperature was controlled to be 300°C; tetraethyl orthosilicate (TEOS) was vaporized at a temperature of 110°C and introduced into the vacuum deposition chamber at a flow rate of 300μl / min; at the same time, the temperature of the water-cooled sample stage, the chamber pressure, and the flow rates of helium and oxygen were kept unchanged;
[0080] Turn off the nickel-chromium hot wire heating power supply, turn off the helium flow, maintain the oxygen flow at 90 sccm, and maintain the chamber pressure at 100 mTorr; turn on the copper rod electrode pulse plasma discharge again, with a discharge time of 30 s and a discharge power of 300 W;
[0081] After the coating was completed, the temperature and vacuum were maintained unchanged. After 30 minutes, the vacuum was broken and the silicon wafer and glass plate samples were taken out. The coating thickness of the silicon wafer was tested. The water contact angle test results of the coating on the glass plate samples are listed in Table 1 below. At room temperature, the glass plate samples were immersed in water for different time periods and then naturally dried. The water contact angle test results are listed in Table 2 below. The anti-fog test results of the coated (coated) glass plate samples and the uncoated blank glass plate samples are shown in Table 2 below. Figure 3 shown.
[0082] Comparative Example 1
[0083] A transparent glass plate (length: 13 cm, width: 6.5 cm, thickness: 1 mm) and a silicon wafer were placed in a PECVD vacuum reaction chamber. The reaction chamber was continuously evacuated to a vacuum degree of 80 mTorr. The temperature inside the chamber was 45°C. Helium was introduced at a flow rate of 40 sccm.
[0084] The chamber pressure was maintained at 80 mTorr, the helium flow rate was maintained at 40 sccm, and the RF plasma discharge was turned on to pre-treat the surface of the transparent glass plate. The RF energy output mode was continuous discharge, the discharge time was 300 s, and the discharge power was 300 W.
[0085] Then, 1,4-butenediol was introduced, the monomer flow rate was 120 μL / min, the monomer vaporization temperature was 110°C, the chamber pressure was maintained at 80 mTorr, the helium flow rate was maintained at 40 sccm, and the RF plasma discharge was turned on. The RF energy output mode was pulsed, the discharge time was 5400 s, the discharge power was 80 W, the pulse frequency was 50 Hz, and the pulse duty cycle was 45%;
[0086] After the coating preparation is completed, the reaction chamber is restored to normal pressure, the chamber is opened to take out the silicon wafer and glass plate samples, the coating thickness of the silicon wafer is tested, and the water contact angle test results of the coating on the glass plate sample are listed in Table 1 below. At room temperature, the glass plate sample is immersed in water for different time periods, and then naturally dried and the water contact angle test results are listed in Table 2 below.
[0087] Comparative Example 2
[0088] A transparent glass plate (length: 13 cm, width: 6.5 cm, thickness: 1 mm) and a silicon wafer were placed in a PECVD vacuum reaction chamber. The reaction chamber was continuously evacuated to a vacuum degree of 80 mTorr. The temperature inside the chamber was 45°C. Helium was introduced at a flow rate of 40 sccm.
[0089] The chamber pressure was maintained at 80 mTorr, the helium flow rate was maintained at 40 sccm, and the RF plasma discharge was turned on to pre-treat the surface of the transparent glass plate. The RF energy output mode was continuous discharge, the discharge time was 300 s, and the discharge power was 300 W.
[0090] Then, 1,4-butenediol and methacrylamide were mixed in a mass ratio of 5:1, stirred at room temperature for 10 minutes to mix evenly, then introduced into the vaporization chamber for vaporization and then introduced into the PECVD vacuum reaction chamber, the monomer flow rate into the vaporization chamber was 120 μL / min, the monomer vaporization temperature was 110°C, the chamber pressure was maintained at 80 mTorr, the helium flow rate was maintained at 40 sccm, and the RF plasma discharge was turned on. The RF energy output mode was pulsed, the discharge time was 1800 s, the discharge power was 80 w, the pulse frequency was 50 Hz, and the pulse duty cycle was 45%;
[0091] After the coating preparation is completed, the reaction chamber is restored to normal pressure, the chamber is opened to take out the silicon wafer and glass plate samples, the coating thickness of the silicon wafer is tested, and the water contact angle test results of the coating on the glass plate sample are listed in Table 1 below. At room temperature, the glass plate sample is immersed in water for different time periods, and then naturally dried and the water contact angle test results are listed in Table 2 below.
[0092] Comparative Example 3
[0093] A transparent glass plate (length: 13 cm, width: 6.5 cm, thickness: 1 mm) and a silicon wafer were placed in a PECVD vacuum reaction chamber. The reaction chamber was continuously evacuated to a vacuum degree of 80 mTorr. The temperature inside the chamber was 45°C. Helium was introduced at a flow rate of 40 sccm.
[0094] Then, tetraethyl orthosilicate (TEOS) was introduced, the monomer flow rate was 45 μL / min, the monomer vaporization temperature was 110°C, the chamber pressure was maintained at 80 mTorr, the helium flow rate was maintained at 40 sccm, and the RF plasma discharge was turned on. The RF energy output mode was pulsed, the discharge time was 3600 s, the discharge power was 80 W, the pulse frequency was 50 Hz, and the pulse duty cycle was 45%;
[0095] After the coating preparation is completed, the reaction chamber is restored to normal pressure, the chamber is opened to take out the silicon wafer and glass plate samples, the coating thickness of the silicon wafer is tested, and the water contact angle test results of the coating on the glass plate sample are listed in Table 1 below. At room temperature, the glass plate sample is immersed in water for different time periods, and then naturally dried and the water contact angle test results are listed in Table 2 below.
[0096] Comparative Example 4
[0097] A transparent glass plate (length: 13 cm, width: 6.5 cm, thickness: 1 mm) and a silicon wafer were placed on a sample stage of a vacuum deposition chamber equipped with a pair of copper rod electrodes. The vacuum deposition chamber was evacuated to a vacuum degree of 8 mTorr, and the sample stage temperature was controlled to about 30°C by water cooling. Helium was introduced at a flow rate of 90 sccm and a chamber pressure of 100 mTorr.
[0098] The nickel-chromium hot wire power supply was turned on and the hot wire temperature was controlled to be 300°C; tetraethyl orthosilicate (TEOS) was vaporized at a temperature of 110°C and introduced into the vacuum deposition chamber at a flow rate of 300 μl / min; at the same time, the temperature of the water-cooled sample stage, the chamber pressure, and the flow rates of helium and oxygen were kept unchanged;
[0099] After the coating was completed, the temperature and vacuum were maintained unchanged. After 30 minutes, the vacuum was broken and the silicon wafer and glass plate samples were taken out. The coating thickness of the silicon wafer was tested, and the water contact angle of the glass plate sample was tested. The results are listed in Table 1 below. At room temperature, the glass plate samples were immersed in water for different time periods, and then naturally dried and the water contact angle test results were listed in Table 2 below.
[0100] Table 1 Test results of coating thickness and water contact angle of Examples 1-3 and Comparative Examples 1-4
[0101] Coating thickness (nm) Water contact angle (°) Example 1 42 3 Example 2 55 5 Example 3 34 3 Comparative Example 1 48 5 Comparative Example 2 53 7 Comparative Example 3 41 95 Comparative Example 4 30 20
[0102] Table 2 Test results of water contact angles of coatings of glass plate samples of Examples 1-3 and Comparative Examples 1-4 at different immersion times
[0103]
[0104] According to the results in Tables 1 and 2 above, in Examples 1-3, the hydrophilic coating formed by hot wire chemical vapor deposition of the organic silicon monomer tetraethyl orthosilicate on the surface of the substrate under an oxygen atmosphere has excellent hydrophilic properties, and its water contact angle is below 5°, and the water contact angle of the coating can still be maintained below 10° after being immersed in water for 180 minutes, indicating that it has excellent hydrophilic retention in a high humidity environment. In Comparative Examples 1-2, although a coating with excellent hydrophilic properties can be obtained by plasma polymerization coating using a hydrophilic monomer, its hydrophilicity is significantly attenuated after being immersed in water for 10 minutes, indicating that its hydrophilic retention in a high humidity environment is relatively poor. In Comparative Example 3, the water contact angle of the coating using plasma polymerization or tetraethyl orthosilicate is 95°, indicating that it is not hydrophilic. In Comparative Example 4, tetraethyl orthosilicate is not subjected to hot wire chemical vapor deposition in an oxygen atmosphere, and its water contact angle is 20°, indicating that its coating has relatively poor hydrophilicity. By comparing the results of Examples 1-3, in Example 3, the glass plate with a plasma pre-treatment step and a plasma post-treatment step in an oxygen atmosphere has better hydrophilicity retention in a high humidity environment than the glass plate with only a plasma pre-treatment step in Example 1, and the glass plate sample with only a plasma pre-treatment step has better hydrophilicity and hydrophilicity retention in a high humidity environment than the glass plate sample with no plasma pre-treatment step and post-treatment step in Example 2, indicating that the plasma pre-treatment step is beneficial to improving the hydrophilicity of the coating and the hydrophilicity retention in a high humidity environment, and the plasma post-treatment step in an oxygen atmosphere can further improve the hydrophilicity retention of the coating in a high humidity environment. Figure 1-Figure 3 The results show that the coatings in Examples 1-3 have excellent anti-fog properties.
[0105] Although the disclosure is disclosed as above, the disclosure is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the disclosure, so the protection scope of the disclosure should be based on the scope defined by the claims.
Claims
1. A hydrophilic coating, characterized in that: The water contact angle of the hydrophilic coating is below 10°, and the hydrophilic coating is formed by hot wire chemical vapor deposition of organic silicon monomers on the surface of the substrate under an oxygen atmosphere; The water contact angle of the hydrophilic coating after being immersed in water at room temperature for 120 minutes is below 10°.
2. The hydrophilic coating according to claim 1, characterized in that: The water contact angle of the hydrophilic coating is below 5°.
3. The hydrophilic coating according to claim 1, characterized in that: The organic silicon monomer is selected from at least one of the structures in the following formulas (1) to (3), ; In the above formulae (1) to (3), R1, R5 and R9 are independently selected from C1-C 10 Alkyl or C1-C 10 Alkoxy, R2, R3, R4, R6 and R 10 are independently selected from hydrogen atoms, C1-C 10 Alkyl or C1-C 10 Alkoxy, R7 is a hydrogen atom, a hydroxyl group, a C1-C 10 Alkyl or C1-C 10 Alkoxy, R8 is a hydrogen atom or a C1-C 10 wherein n is an integer from 1 to 10, and m is an integer from 1 to 10.
4. The hydrophilic coating according to claim 3, characterized in that: The organosilicon monomer has a structure as shown in formula (1), and R1, R2, R3 and R4 are independently selected from C1-C4 alkoxy groups.
5. The hydrophilic coating according to claim 4, characterized in that: The organic silicon monomer is ethyl orthosilicate, tetramethoxysilane, propyl orthosilicate or butyl orthosilicate.
6. The hydrophilic coating according to claim 1, characterized in that: The boiling point of the organic silicon monomer is below 200°C.
7. The hydrophilic coating according to claim 1, characterized in that: The thickness of the hydrophilic coating is 5nm to 3000nm.
8. A method for preparing a hydrophilic coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: placing the substrate on a sample stage with a cooling device in a vacuum deposition chamber; The vacuum deposition chamber is evacuated, oxygen, inert gas and organosilicon monomer gas are introduced, and the heating wire heating and the cooling device are turned on to carry out the hot wire chemical vapor deposition.
9. The method for preparing a hydrophilic coating according to claim 8, characterized in that: The heating wire is a metal wire containing at least one of nickel, chromium or tungsten.
10. The method for preparing a hydrophilic coating according to claim 8, characterized in that: The temperature of the sample stage is controlled below 100°C, and the temperature of the heating wire is 200-900°C.
11. The method for preparing a hydrophilic coating according to claim 8, characterized in that: The following steps are also included: Before the hot wire chemical vapor deposition, the surface of the substrate is subjected to plasma pretreatment.
12. The method for preparing a hydrophilic coating according to claim 8, characterized in that: The following steps are also included: After the hot wire chemical vapor deposition, a plasma post-treatment is performed on the surface of the hot wire chemical vapor deposition coating in an oxygen atmosphere.
13. The method for preparing a hydrophilic coating according to claim 11 or 12, characterized in that: The plasma is a dual-electrode pulsed plasma.
14. A device having a hydrophilic coating, characterized in that: At least part of the surface of the device has the hydrophilic coating according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for coating a substrate using plasma
CN101048237A
Preparation method of organosilicone nano protective coating
CN107523808A